Semaphorin 3C exacerbates liver fibrosis - De Angelis Rigotti, Francesca; Wiedmann, Lena; Hubert, Max Ole; Vacca, Margherita; Safatul Hasan, Sana; Moll, Iris; Carvajal, Silvia; Jiménez, Wladimiro; Starostecka, Maja; Billeter, Adrian; Müller, Beat P.; Wolff, Gretchen; et al. (Hepatology, 2023)
Background and Aims: Chronic liver disease is a growing epidemic, leading to fibrosis and cirrhosis. TGF-β is the pivotal profibrogenic cytokine that activates HSC, yet other molecules can modulate TGF-β signaling during liver fibrosis. Expression of the axon guidance molecules semaphorins (SEMAs), which signal through plexins and neuropilins (NRPs), have been associated with liver fibrosis in HBV-induced chronic hepatitis. This study aims at determining their function in the regulation of HSCs. Approach and Results: We analyzed publicly available patient databases and liver biopsies. We used transgenic mice, in which genes are deleted only in activated HSCs to perform ex vivo analysis and animal models. SEMA3C is the most enriched member of the semaphorin family in liver samples from patients with cirrhosis. Higher expression of SEMA3C in patients with NASH, alcoholic hepatitis, or HBV-induced hepatitis discriminates those with a more profibrotic transcriptomic profile. SEMA3C expression is also elevated in different mouse models of liver fibrosis and in isolated HSCs on activation. In keeping with this, deletion of SEMA3C in activated HSCs reduces myofibroblast marker expression. Conversely, SEMA3C overexpression exacerbates TGF-β-mediated myofibroblast activation, as shown by increased SMAD2 phosphorylation and target gene expression. Among SEMA3C receptors, only NRP2 expression is maintained on activation of isolated HSCs. Interestingly, lack of NRP2 in those cells reduces myofibroblast marker expression. Finally, deletion of either SEMA3C or NRP2, specifically in activated HSCs, reduces liver fibrosis in mice. Conclusion: SEMA3C is a novel marker for activated HSCs that plays a fundamental role in the acquisition of the myofibroblastic phenotype and liver fibrosis.